The effectiveness of cadastre updating in Poland - Dawidowicz, Agnieszka; Dawidowicz, Karol (International Conference “Environmental Engineering”, 2017)
In developed societies cadastre is fundamental and reference system on land for other land information systems. It protects the legal boundaries of the properties. It is also significant from the point of view of property tax es, urban planning and development of real estate markets. It is important that cadastre reflects the current status on the ground. Any changes in both the physical and legal space relating to real estate should be immediately updated in the system. The article presents the study on the effectiveness of cadastre updating in Poland. The effectiveness of updating cadastral data was examined from the point of view of determined criteria as a case study on the example of two municipalities. The research has shown that the current process of updating cadastre in Poland is far from ideal. The repair solutions were suggested.
Keywords: cadastral systems; update; automation; integrated land information systems